Analysis of competitive activity in the greco-roman wrestling - Tropin, Y.; Kovalenko, J. (International Journal of Wrestling Science, 2022)
PURPOSE: to carry out a study and comparative analysis of the competitive activity indicators of the Greco-Roman style wrestlers of a high level of skill of different weight groups to identify trends in the dynamics of technical actions and technical and tactical preparedness.